Formative assessment: component of teaching-learning process in the university context in post-COVID-19 - Martínez Huamán, Edgar Luis (2022)
The aim of this study was to reveal formative assessments as being a component of the teaching-learning process in the university context in post-COVID-19 times. This study has focused on the qualitative approach through the interpretive phenomenological method. The data gathering tool used was that of a semi-structured interview with seven professors from the education and engineering programs at the Universidad Nacional José María Arguedas, Peru. The methodological procedure involved the organization through the Atlas.ti computer program and the transcription of the information through content analysis, resulting in the emergence of validated categories through the triangulation process reflecting the phenomenological reduction. The results showed there to be three categories: the role of the professor in the formative assessment, socio-emotional bonding, and learning feedback. In conclusion, formative assessment is a fundamental component of teaching and learning in the classroom where the professor, through feedback in the class sessions, promotes socio-emotional bonding, perceives mistakes to offer correction, and recognizes the work well done to encourage reinforcement and reflection of the teaching practice. A new evaluative culture focused on the formation of skills and competencies is required for which the professor has a high commitment and responsibility not only in terms of preparing and training the student but also themselves.